Microalgae Synthesize Hydrocarbons from Long-Chain Fatty Acids via a Light-Dependent Pathway . Issue 4 (10th June 2016) - Sorigué, Damien; Légeret, Bertrand; Cuiné, Stéphan; Morales, Pablo; Mirabella, Boris; Guédeney, Geneviève; Li-Beisson, Yonghua; Jetter, Reinhard; Peltier, Gilles; Beisson, Fred
Abstract : A pathway converting C16 and C18 fatty acids to alkanes or alkenes, involving the light-dependent transformation of cis-vaccenic acid into 7-heptadecene, is present in various microalgae. Abstract: Microalgae are considered a promising platform for the production of lipid-based biofuels. While oil accumulation pathways are intensively researched, the possible existence of a microalgal pathways converting fatty acids into alka(e)nes has received little attention. Here, we provide evidence that such a pathway occurs in several microalgal species from the green and the red lineages. In Chlamydomonas reinhardtii (Chlorophyceae), a C17 alkene, n -heptadecene, was detected in the cell pellet and the headspace of liquid cultures. The Chlamydomonas alkene was identified as 7-heptadecene, an isomer likely formed by decarboxylation of cis-vaccenic acid. Accordingly, incubation of intact Chlamydomonas cells with per-deuterated D31 -16:0 (palmitic) acid yielded D31 -18:0 (stearic) acid, D29 -18:1 (oleic and cis-vaccenic) acids, and D29 -heptadecene. These findings showed that loss of the carboxyl group of a C18 monounsaturated fatty acid lead to heptadecene formation. Amount of 7-heptadecene varied with growth phase and temperature and was strictly dependent on light but was not affected by an inhibitor of photosystem II. Cell fractionation showed that approximately 80% of the alkene is localized in the chloroplast. Heptadecane, pentadecane, as well as 7- and 8-heptadecene were detected in Chlorella variabilis NC64A (Trebouxiophyceae) and several Nannochloropsis species (Eustigmatophyceae). In contrast, Ostreococcus tauri (Mamiellophyceae) and the diatom Phaeodactylum tricornutum produced C21 hexaene, without detectable C15 -C19 hydrocarbons. Interestingly, no homologs of known hydrocarbon biosynthesis genes were found in the Nannochloropsis, Chlorella, or Chlamydomonas genomes. This work thus demonstrates that microalgae have the ability to convert C16 and C18 fatty acids into alka(e)nes by a new, light-dependent pathway.